One-step and two-step qPCR assays for CAPRV2023: development and application in full-cycle epidemiological surveillance of golden pompano - Sun, Heng; Fred, Bissih; Wang, Haoyu; Huang, Jie; Wu, Zihao; Wu, Dandan; Lu, Yishan; Jian, Jichang; Huang, Yucong (Frontiers in Veterinary Science, 2025)
Carpione rhabdovirus strain 2023 (CAPRV2023) has recently emerged as a significant pathogen responsible for substantial mortality in farmed golden pompano (Trachinotus ovatus) across China, threatening the sustainability of the aquaculture industry. To address the urgent need for rapid and accurate diagnostics, we developed two TaqMan probe-based quantitative PCR (qPCR) assays targeting the viral G protein gene: a two-step qPCR assay and a one-step qPCR assay. The newly developed two-step qPCR assay demonstrated excellent performance, with a detection limit of 2 copies/μL and an amplification efficiency of 104.7%. The intra- and inter-assay coefficients of variation (CVs) ranged from 0.23 to 0.95% and 0.28 to 1.95%, respectively. The one-step qPCR assay further simplified the detection workflow by integrating reverse transcription and amplification into a single closed-tube reaction. It achieved a detection limit of 15 copies/μL, with a high amplification efficiency (102.8%) and excellent repeatability (CV = 0.81%). Specificity tests demonstrated that no cross-reactivity was observed with other aquatic pathogens. Extensive validation across clinical and environmental samples revealed that the two-step and one-step qPCR assays consistently exhibited higher detection sensitivity than conventional PCR. Their reliable performance across multiple geographic locations and sampling periods confirmed robust diagnostic reliability, indicating strong tolerance to potential viral mutations and excellent adaptability to diverse aquaculture environments. In addition, the two qPCR assays enabled accurate quantification of viral loads in aquaculture water samples concentrated via ultrafiltration, demonstrating their value in environmental surveillance. Overall, both the two-step and one-step qPCR assays represent robust, sensitive, and field-adaptable diagnostic platforms, with extensive applications in disease surveillance, early outbreak warning, pathogenesis studies, and aquaculture biosecurity.